(untitled) (Gestão & Regionalidade, 2018)
This study aims at identifying the relation between corporate governance practices and performance by public companies in the construction and engineering subsector, in the transportation and construction sector, at the BM&FBovespa. In order to do so, the research gathers financial data from 30 companies, referring to 2013, and collected from the BM&FBovespa website and from the EconomáticaÂ® base. Concerning corporate governance, an index calculated by means of a checklist proposed by literature also referring to 2013 was used. Research shows that the corporate governance index influences positively business, economic (ROE), operational (Ebtida/Asset), and value (Tobin’s Q), performance. Thus, the study offers empirical evidence of corporate governance impact on business performance in the construction and engineering subsector at BM&FBovespa, which suggests that the good practices of corporate governance are fundamental for organization, and must be promoted for the benefit of investors and other stakeholders. Keywords: Corporate governance; business performance; construction and engineering.